HUBUNGAN PENGGUNAAN OBAT ANTIHIPERTENSI (DIURETIK TIAZID & DIURETIK KUAT) SEBAGAI FAKTOR RISIKO TERJADINYA ARTRITIS GOUT PADA PASIEN USIA 40 – 75 TAHUN DI RUMAH SAKIT ISLAM CEMPAKA PUTIH TAHUN 2013 – 2015 - Farhan, Fanny Septiani; Raihana, Rifka (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Gout Arthritis is a crystal deposition disease which arises when supersaturation of body tissues with urate occurs, leading to the formation of monosodium urate crystals (MSU) in and around joints. Many factors can cause a risk factors for the development of gout, including diuretic drugs that can be used to patients with hypertension.the aim of this study is to determine the relationship antihypertensive drugs use (thiazide diuretics & loop diuretics) as a risk factor of incident gout arthritis at patients aged 40 – 75 years in Islamic Hospital of Jakarta Cempaka Putih period 2013 – 2015. This study used a cross-sectional study design. The total sample of 75 with a simple random sampling with lottery technique and data analysis using a Chi-Square test. The study was conducted in the Islamic Hospital of Jakarta Cempaka Putih in Oktober 2015. The prevalence of gout arthritis at patients aged 40 – 75 years in RSIJCP as much as 57 people (76%). And there is a significant relationship between antihypertensive drugs use (thiazide & loop diuretics) with an incident of gout arthritis with p-value 0.013 CI 95%: 1.295 – 13.209 and OR 4.14. as conclusion, Thiazide diuretics and loop diuretics were associated with increased gout arthritis risk at patients aged 40 – 75 years in Islamic Hospital of Jakarta Cempaka Putih (RSIJCP) period 2013 – 2015.